Electrical transport mechanism in boron nitride thin film - Ozdemir, Orhan; Anutgan, Mustafa; Aliyeva-Anutgan, Tamila; Atilgan, Ismail; Katircioglu, Bayram (ELSEVIER, 2009)
Both dc and ac transport characteristics of plasma enhanced chemical vapor deposited (PECVD) boron nitride (BN) thin film was investigated by dc current vs. dc voltage measurement at different temperatures and admittance vs. gate voltage at various frequencies/temperatures, respectively. MIM metal (Al)-insulator (BN)-metal (Al) or MIS metal (Al)-BN-semiconductor (p-Silicon) test devices were conventionally produced. Both conductivity anisotropy and dc/ac detailed transport mechanism were analyzed within the frame of a turbostratic structure (t-BN), interfacing the substrate by a thin amorphous layer (a-BN). This defective BN film has been justified by both infrared (IR) analysis and indirectly by the resulting electrical transport behavior. Transport and its Variations as a function of temperature/frequency are in agreement with a hopping mechanism across Gauss-like energy distributed localized deep traps. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alloys; III-V semiconductors; Heterojunctions; Band structure; Conductivity; Defects; FTIR measurements; CHARGE-TRANSPORT; BAND-STRUCTURE; HOPPING MODEL; ENERGY; Materials Science